Pandangan Wahbah Al-Zuḥaylī terhadap Musik dalam Surah Luqman Ayat 6: Analisis al-Tafsīr al-Munīr fī al-ʻAqīdah wa asy-Syarīʻah wa al-Manhaj - Muhammad Surya; Amroeni Drajat; Husnel Anwar Matondang (Yayasan Albahriah Jamiah Indonesia, 2026)
The debate regarding the meaning of lahw al-Ḥadīth in Surah Luqman verse 6 continues to be a crucial point in the discourse on music law in Islam, especially due to the differences in classical and contemporary interpretations involving linguistic, normative, and sociocultural dimensions. This paper aims to analytically examine the construction of the meaning of lahw al-Ḥadīth, the normative position of music, and the methodological character of Wahbah al-Zuḥaylī’s interpretation in al-Tafsīr al-Munīr fī al-ʻAqīdah wa ash-Sharīʻah wa al-Manhaj. The approach used is a qualitative one based on a literature study with content analysis methods and a thematic interpretation approach to trace the argumentation patterns and epistemological framework used. The results show that al-Zuḥaylī does not simplistically identify lahw al-Ḥadīth as music, but rather understands it as any form of speech or practice that leads astray from the path of truth, including but not limited to singing containing negative elements. Within his normative framework, music is not positioned as an inherently forbidden entity, but rather depends on its content, purpose, and impact on individual and societal morality. Methodologically, al-Zuḥaylī’s interpretation demonstrates a systematic integration between the bi al-Maʻthūr and bi al-Raʻyi tafsir approaches with a moderate fiqh orientation, resulting in a contextual and proportionate legal formulation. The theoretical implication lies in strengthening the integrative tafsir paradigm that can bridge normative texts with contemporary realities in Islamic legal studies.